A pilot study documenting increased thrombin generation following abrupt withdrawal of heparin therapy in healthy dogs. Issue 6 (10th October 2018) - Mays, Erin M.; Dorman, David C.; McKendry, Colleen; Hanel, Rita M.
Abstract: Objective: To document if a transient hypercoagulable state occurs in healthy dogs following abrupt cessation of unfractionated heparin (UFH) therapy. Design: Prospective experimental pilot study. Setting: University research facility. Animals: Seven adult random‐source male dogs. Intervention: Thromboelastography (TEG) and thrombin–antithrombin (TAT) complex formation were used to assess coagulation status in healthy dogs. Seven adult research dogs received 200–300 IU/kg subcutaneous UFH every 8 hours for 4 days. A final IV bolus of 100 IU/kg was given on day 4 and the peak measured heparin concentration 1 hour later is defined as the start of heparin withdrawal (time 0). Citrated whole blood samples were collected at baseline (prior to heparin administration) and 3, 6, 12, 30, and 48 hours after UFH withdrawal. At all time points, a kaolin‐activated TEG was performed and citrated plasma for measurement of TAT concentration was collected for batch analysis. Fibrinogen concentration, PCV, total plasma proteins, and platelet count were measured at baseline and 48 hours after heparin withdrawal. Measurements and Main Results: Compared to baseline, TAT was increased 12 hours after heparin withdrawal and returned to baseline by 30 hours. TEG clot formation time (K) was decreased 30 and 48 hours after heparin withdrawal. Conclusion: TAT results suggest that a transient increase in thrombin generation developed 12 hours after withdrawal of UFH therapy. Though clot kinetics were rapid compared to baseline beginning 30 hours after heparin withdrawal, a return to baseline was not documented. Future studies are warranted to determine the clinical relevance of these results and to evaluate the effect of UFH withdrawal in critically ill animals.